2021
DOI: 10.1155/2021/5519847
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pathogens and Their Antimicrobial Resistance Patterns of Inanimate Surfaces and Equipment in Ethiopia: A Systematic Review and Meta-analysis

Abstract: Background. Hospital-acquired infections have remained a serious cause of mortality, morbidity, and extended hospitalization. Bacterial contamination of inanimate surfaces of the hospital environment and equipment is considered a major contributing factor to the development of several nosocomial infections worldwide. The hospital environment and many devices are an important reservoir of many clinically important bacterial agents including multidrug-resistant pathogens. Therefore, this systematic review and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(113 reference statements)
0
3
2
Order By: Relevance
“…However, this fnding was higher than previous studies done in Morocco (26.8%) [35], Palestine (24.7%) [36], and Egypt (25.6%) [37]. In contrast, this fnding was lower than previous studies conducted in Ethiopia (70%) [31], Northern Ethiopia [15], Jimma (66%) [16], Eastern Ethiopia (53.8%), Addis Ababa (86%) [38], Zimbabwe (86.21%) [39], and Nigeria (56.7%) [40]. Tis variation could be due to differences in the infection management systems of hospitals within or in diferent countries, hygiene practices of the population in the hospital environment, architecture characteristics, sample size, and microbial characteristics.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…However, this fnding was higher than previous studies done in Morocco (26.8%) [35], Palestine (24.7%) [36], and Egypt (25.6%) [37]. In contrast, this fnding was lower than previous studies conducted in Ethiopia (70%) [31], Northern Ethiopia [15], Jimma (66%) [16], Eastern Ethiopia (53.8%), Addis Ababa (86%) [38], Zimbabwe (86.21%) [39], and Nigeria (56.7%) [40]. Tis variation could be due to differences in the infection management systems of hospitals within or in diferent countries, hygiene practices of the population in the hospital environment, architecture characteristics, sample size, and microbial characteristics.…”
Section: Discussioncontrasting
confidence: 78%
“…The sample size was calculated using a single population proportion formula considering the 95% level taking the prevalence of 70% from a previous study [ 31 ] and degree of allowable error 0.05. The sample size is therefore calculated as follows: where N = sample size.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the present study, Acinetobacter species, A. baumannni was the most persistently detected isolate in ICUs [25,26]. Moreover, a systematic review and meta-analysis that estimated the overall prevalence of bacterial contamination on inanimate surfaces and equipment in Ethiopia reported that E. coli was the most commonly detected isolate, followed by P. aeruginosa and K. pneumoniae [27]. This inconsistency with the results of other studies on the number and type of isolates may be due to differences in the number of people in the environment, amount of activity, amount of moisture, presence of material capable of supporting microbial growth, and type of environmental surface (for example, rough or smooth), and orientation in ICUs [11].…”
Section: Discussioncontrasting
confidence: 99%
“…aeruginosa and K . pneumoniae [ 27 ]. This inconsistency with the results of other studies on the number and type of isolates may be due to differences in the number of people in the environment, amount of activity, amount of moisture, presence of material capable of supporting microbial growth, and type of environmental surface (for example, rough or smooth), and orientation in ICUs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Ahmed et al [28] and Kiros et al [41] point out that strains of Klebsiella pneumoniae are relatively common on inanimate surfaces. However, in our study, only two strains of K. pneumoniae (DAIC, n = 1; DIM, n = 1) were identified from inanimate surfaces.…”
Section: Discussionmentioning
confidence: 99%